Degradação por vibração em alvenaria de tijolo cerâmico : o impacto do tráfego viário no Sítio Histórico de Santa Leopoldina-ES - Dornelas, Angélica Maria Fonseca (2017)
The objective of this work is to investigate the deterioration of historic buildings built in ceramic brick masonry, due to cracking and its correlation with the impact of mechanical vibrations generated by road traffic. It presents as object the Historic